#TITLE_ALTERNATIVE# - HIDAYAT (NIM : 12212082), SATRIA
Enhanced Geothermal System (EGS) applied on Hot Dry Rock geothermal formation (HDR). Although it has considerable availability in nature, the HDR formation is an impermeable layer of basement rock, so to exploit the energy it needs to make the formation as an artificial reservoir, by improving its rock properties, especially permeability and porosity. Hydraulic fracturing becomes the solution in this problem by making fractures in the formation so that there is interconnected space to pass through the fluid as a material that brings heat energy from within the formation. This paper discusses the most optimum operating design on hydraulic fracturing activities for hot dry rock (HDR) formation in consideration of Fcd value. The designs will simulate using FracCADE 5.1 software with hydraulic fracturing material taken from a field case study. The simulation will be done with PKN geometry model. From sensitivity analysis result we know that proppant 12/18 CarboHSP-2000 using pumping rate 20 bpm and maximum proppant concentration 15.0 PPA give highest Fcd.